Fregoli Syndrome: An Underrecognized Risk Factor for Aggression in Treatment Settings - Ashraf, Nauman; Antonius, Daniel; Sinkman, Arthur; Kleinhaus, Karine; Malaspina, Dolores (Case Reports in Psychiatry, 2011)
Fregoli syndrome (FS) is commonly associated with verbal threats and aggressive behavior. We present a case of Fregoli syndrome leading to an assault. We discuss the possible underdiagnosis of FS, associated risk for aggression, and strategies to reduce that risk.